2005
DOI: 10.1145/1039174.1039200
|View full text |Cite
|
Sign up to set email alerts
|

Testing web applications focusing on their specialties

Abstract: Nowadays, Web applications are very prevalent around the world, and it becomes more and more important to ensure their qualities by testing. However, due to the special characters of Web applications, traditional testing methods are not suitable for Web testing in many aspects. So based on the related work by now, this paper presents our research work in such areas as the Web application modeling, the test case generation, the detailed testing methods and techniques, the testing executing process, and the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
(32 reference statements)
0
10
0
7
Order By: Relevance
“…However, realism in the simulation of user behaviour for the purpose of load testing has been found to be crucial [29,1]. "A load test is valid only if virtual users' behaviour has characteristics similar to those of actual users" because "failure to mimic real user behaviour can generate totally inconsistent results" [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, realism in the simulation of user behaviour for the purpose of load testing has been found to be crucial [29,1]. "A load test is valid only if virtual users' behaviour has characteristics similar to those of actual users" because "failure to mimic real user behaviour can generate totally inconsistent results" [16].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the research effort found in the literature has been concentrated in applying traditional QA measures to web-based software. In particular, several tools and techniques have been developed to assess the functionality and performance of web applications including general frameworks [53,42,40,52] and test case generation strategies [2], to the application of traditional white-box testing techniques [47,39], object-oriented based strategies [28], and statistical testing approaches [24]. Although the pursuit of web quality is a unifying factor between the cited work and the research presented in this thesis, none of the fore mentioned approaches concentrates on how to detect configuration faults before web applications are fielded.…”
Section: Web Testingmentioning
confidence: 99%
“…In the simulation of user behavior for the purpose of load testing it has been found to be crucial [3], [33]. "A load test is valid only if virtual users' behavior has characteristics similar to those of actual users" because "failure to mimic real user behavior can generate totally inconsistent results" [20].…”
Section: B Realismmentioning
confidence: 99%